The Effect of Disclosure of Corporate Social Responsibility, Managerial Ownership, and Institutional Ownership on Company Value (Study on Consumer Goods Industry Sector Companies Listed on the Indonesia Stock Exchange (IDX) for the 2015-2019 Period) - Winda Merliana (Journal of Islamic Economics and Social Science (JIESS), 2021)
This study aimed to investigate the influence of managerial ownership, institutional ownership, and corporate social responsibility to firm value. Firm value in this study as a proxy for the Price Book Value. Collecting data using a purposive sampling method for consumer goods industry sector companies listed in Indonesia Stock Exchange in 2015 until 2019. A total of 65 consumer goods industry sector companies used as a sample. The method of analysis of this study used multiple regression. The result of this study indicates that corporate social responsibility and institutional ownership have an effect on firm value. While managerial ownership has no effect on firm value.